Biosynthesis Of Gold Nanoparticles Of Ixora Coccinea Flower Extract & Their Antimicrobial Activities - NAGARAJ B,; KRISHNAMURTHY NB,; LINY P,; DIVYA TK,; DINESH R, (International Journal of Pharma and Bio Sciences, 2011)
The synthesis of eco-friendly nanoparticles is evergreen branch of nanoscience for biomedical application. Low cost of synthesis and non toxicity are the main features which make it more attractive potential option for biomedical field. Here, we report the synthesis of gold nanoparticles in aqueous medium using flower extracts of Ixora coccinea (Chetty flower) as reducing and stabilizing agent. On treating chloroauric acid solution with extract, rapid reduction of chloroaurate ions is observed leading to the formation of the highly stable gold nanoparticles in solution. The synthesized nanoparticles are confirmed by color changes and it has been characterized by UV-visible spectroscopy. The UV- visible spectra indicate a strong Plasmon resonance that is located at ~550 nm. Presence of this strong broad plasmon peak has been well documented for various Me- NPs, with sizes ranging all the way from 2 to 100 nm. The morphology and size of the biologically synthesized gold nanoparticles were determined using TEM. The images clearly show that the average size of the nanotriangles is about 200 nm, while, the spherical like particles show very small size about 5-10 nm. The study also shows that gold nanoparticles with antibiotic show more inhibitory zones than compared to the standard antibiotics.